Application of Preoperative Ultrasonography in the Percutaneous Minimally Invasive Repair of Acute Closed Achilles Tendon Rupture. - Wang, Zhuang; Chen, Weiwei; Jia, Honglei; Hu, Fangning; Wang, Bomin; Yang, Yongliang; Liu, Fanxiao (BioMed Research International, 2023)
Percutaneous minimally invasive surgery involving Achilles tendon (AT) repair has the advantages of a low rerupture rate and fewer postoperative complications. However, due to the inability to operate under direct vision, the injury of the small saphenous vein (SSV) and sural nerve (SN) remains largely a high risk involving many challenges. We propose to introduce the preoperative application and advantages of ultrasonography in percutaneous minimally invasive surgery for acute AT rupture. Our results indicated that ultrasonography could locate the position of the SN more accurately and reduce the risk of iatrogenic nerve injury. Compared with the traditional surface markers, the preoperative localization and marking of AT, SSV, and SN in ultrasonography significantly reduced the risk of intraoperative accidental injury to blood vessels and nerves, which could reduce postoperative complications and promote early rehabilitation of patients. We ultimately exploit the properties of ultrasonography in percutaneous minimally invasive surgery to treat Achilles tendon rupture.